Mutational load in carotid body tumor - Anna V. Kudryavtseva; Elena N. Lukyanova; Dmitry V. Kalinin; Andrew R. Zaretsky; Anatoly V. Pokrovsky; Alexander L. Golovyuk; Maria S. Fedorova; Elena A. Pudova; Sergey L. Kharitonov; Vladislav S. Pavlov; Anastasiya A. Kobelyatskaya; Nataliya V. Melnikova; et al. (BMC, 2019)
Abstract Background Carotid body tumor (CBT) is a rare neoplasm arising from paraganglion located near the bifurcation of the carotid artery. There is great intra-tumor heterogeneity, and CBT development could be associated with both germline and somatic allelic variants. Studies on the molecular genetics of CBT are limited, and the molecular mechanisms of its pathogenesis are not fully understood. This work is focused on the estimation of mutational load (ML) in CBT. Methods Using the NextSeq 500 platform, we performed exome sequencing of tumors with matched lymph node tissues and peripheral blood obtained from six patients with CBT. To obtain reliable results in tumors with low ML, we developed and successfully applied a complex approach for the analysis of sequencing data. ML was evaluated as the number of somatic variants per megabase (Mb) of the target regions covered by the Illumina TruSeq Exome Library Prep Kit. Results The ML in CBT varied in the range of 0.09-0.28/Mb. Additionally, we identified several pathogenic/likely pathogenic somatic and germline allelic variants across six patients studied (including TP53 variants). Conclusions Using the developed approach, we estimated the ML in CBT, which is much lower than in common malignant tumors. Identified variants in known paraganglioma/pheochromocytoma-causative genes and novel genes could be associated with the pathogenesis of CBT. The obtained results expand our knowledge of the mutation process in CBT as well as the biology of tumor development.